An analysis of variability in power output during indoor and outdoor cycling time trials - Jeffries, O.; Waldron, M.; Patterson, S. D.; Galna, B. (International Journal of Sports Physiology and Performance, 2019)
Purpose: Regulation of power output during cycling encompasses the integration of internal and external demands to maximize performance. However, relatively little is known about variation in power output in response to the external demands of outdoor cycling. The authors compared the mean power output and the magnitude of power-output variability and structure during a 20-min time trial performed indoors and outdoors. Methods: Twenty male competitive cyclists (VO 2 max 60.4 [7.1] mL/kg·min) performed 2 randomized maximal 20-min time-trial tests: outdoors at a cycle-specific racing circuit and indoors on a laboratory-based electromagnetically braked training ergometer, 7 d apart. Power output was sampled at 1 Hz and collected on the same bike equipped with a portable power meter in both tests. Results: Twenty-minute time-trial performance indoor (280 [44] W) was not different from outdoor (284 [41] W) (P = .256), showing a strong correlation (r = .94; P < .001). Within-persons SD was greater outdoors (69 [21] W) than indoors (33 [10] W) (P < .001). Increased variability was observed across all frequencies in data from outdoor cycling compared with indoors (P < .001) except for the very slowest frequency bin (<0.0033 Hz, P = .930). Conclusions: The findings indicate a greater magnitude of variability in power output during cycling outdoors. This suggests that constraints imposed by the external environment lead to moderate- and high-frequency fluctuations in power output. Therefore, indoor testing protocols should be designed to reflect the external demands of cycling outdoors.